Toxicidade ambiental e degradação do antirretroviral fumarato de tenofovir desoproxila. - Sandra Regina Silva (2020)
Tenofovir deoproxyl fumarate (TDF) is an antiretroviral in the class of nucleotide analogs, one of the components of the treatment of the first line of infection by people with HIV/AIDS. This study aimed to evaluate the potential cytotoxic effects of TDF on the cyanobacterium Microcystis novacekii, the Artemia salina microcrustacean, the bacterium Aliivibrio fischeri and the evaluation of cytotoxicity, genotoxicity and mutagenicity of TDF using the Allium cepa a test system. Still,was to compare biodegradation processes using M. novacekii and oxidative degradation via Fenton's reagent for treatment of TDF residues. Toxicity tests were performed according to international protocols to determine the 50% inhibitory concentration (IC50) of tenofovir disoproxil for the species involved (M. novacekii, A. salina and A. vibrio). In addition, the genotoxic and mutagenic potential of TDF was estimated by exposing Allium cepa seeds to the drug and analysis of cytogenototoxic changes of de radicles by optical microscopy. Biodegradation was assessed by cyanobacterial exposure to non-lethal concentrations of TDF with analytical monitoring of the presence of the drug in cultures using high performance liquid chromatography coupled with HPLC/MS mass spectrometry. For oxidative degradation of TDF, Fenton's reagent was used and the degradation process was monitored by HPLC/MS and total carbon content (TOC) analysis. The concentration of tenofovir desoproxil that led to the growth inhibitory effect (IC50) at 96h of M. novacekii was 161.01 (156.81-165.21) mg L-1. For A. salina species the average inhibition after 24h was 111.82 (103.18-120.45) mg.L-1 and for A. fischeri the IC50 at 15 min was 14.83 (13.87- 15.79) mg L-1, showing that A. fischeri, a decomposing bacterium, was the most sensitive organism to the drug. The results of the A. cepa test indicate the genotoxic potential with the prevalence of chromosomal adhesions and bud and micronucleus at concentrations higher than 26.5 mg.L-1. Biodegradation tests have shown that cyanobacterium M. novacekii showed potential for TDF biodegradation with removal of approximately 90% of the drug (88.7 to 94.1)% in 16 days. Oxidative degradation using Fenton's reagent led to drug degradation with two minute reaction with removal rates ranging from 58.5 to 94.1% but with formation of by-products which were not identified. The results indicate a low cytotoxic potential of TDF for aquatic species as well as low genotoxicity, according to the A. cepa model at residual concentrations compatible with its presence in the environment. Both M. novacekii biodegradation and oxidative degradation were efficient to remove TDF in aqueous solutions, but did not lead to total clearance of the drug in the medium. Both processes are alternatives that can be explored in effluent and sewage treatment plants, reducing the environmental diffusion of these residues. From this study it can be concluded that the low toxicity observed does not guarantee that TDF is an environmentally safe drug, considering its low solubility in aqueous medium, the possibility of sediment accumulation and its resistance to processes of degradation.